MEMORI KOLEKTIF KEISLAMAN MASYARAKAT MELAYU DAN WACANA ANTIKOLONIAL DALAM SYAIR ARDAN W. 262 (Islamic Collective Memory of Malay Society and Anticolonial Discourse in Syair Ardan W. 262) - Resmanti, Maiyang; Kurniawan, Bagus (Kandai, 2024)
How are the collective memories of the Malay society in Syair Ardan? and how are Malay society dreams about responding to colonialism in Syair Ardan? are the main problem. This analysis aims to describe the collective memories of the Malay society in Syair Ardan and the dreams of the Malay society in responding to colonialism in Syair Ardan. The object analyzed is the classic Malay manuscript which was copied during the Islamic era that existed in Malay and the Malay nation had contact with colonial nations, entitled Syair Ardan W. 262 collection of PNRI. The text narrates the collective memories of the Malay society in forming their religious identity and dreams of responding to colonialism. The text is analyzed using collective memory studies regarding consciousness in responding to the socio-culture of a society using the hermeneutical method. This article reveals that Islam is part of the identity of the Malay society which can be proven through the opening narrative, content, and colophon in Syair Ardan, the dreams of the Malay society through collective memory by showing traces of the authority of the Malay nation to the next generation; and a representation of dreams of Islamization of the colonial nation. Bagaimana memori kolektif masyarakat Melayu dalam teks Syair Ardan? dan bagaimana angan-angan masyarakat Melayu merespons kolonialisme dalam teks Syair Ardan? merupakan pokok permasalahan yang menjadi inti dari tulisan ini. Analisis ini bertujuan untuk mendeskripsikan memori kolektif masyarakat Melayu dalam teks Syair Ardan dan menjabarkan angan-angan masyarakat Melayu merespons kolonialisme dalam teks Syair Ardan. Objek yang dianalisis adalah naskah Melayu klasik yang disalin pada masa Islam telah eksis di Melayu dan bangsa Melayu telah bersinggungan dengan bangsa kolonial, berjudul Syair Ardan W. 262 koleksi PNRI. Teks menarasikan memori kolektif masyarakat Melayu dalam membentuk identitas religius dan angan-angan merespons kolonial. Teks dianalisis menggunakan kajian memori kolektif mengenai kesadaran dalam merespons sosial-budaya suatu masyarakat dengan metode hermeneutis, yaitu penginterpretasian suatu objek yang membentuk lingkaran hermeneutis. Tulisan ini mengungkap bahwa Islam adalah bagian dari identitas masyarakat Melayu yang dapat dibuktikan melalui narasi pembuka teks, isi teks, dan kolofon dalam Syair Ardan; angan-angan masyarakat Melayu melalui memori kolektif dengan menunjukkan jejak-jejak kewibawaan bangsa Melayu kepada generasi selanjutnya; dan representasi angan-angan Islamisasi bangsa kolonial.